Credit card ownership and usage among college students - Pellejera, Nicanor Barrientos
This study examined the credit card ownership and usage of college students. The researcher looked at the reasons behind owning and using credit cards including usage patterns and payment practices of the respondents. Problems encountered concerning the use of credit cars were also described. Th Credit Cars Usage survey questionnaire was used to gather the necessary information. Thirty-four college students from different universities and colleges in Metro Manila participated in the study. Data collected were analyzed using descriptive statistics. Findings showed that majority of the respondents acquired credit cars because of convenience and emergencies. According to survey results, mothers played a major role whenever college students decide to acquire credit cards. Mothers were also the primary ones who pay the credit card bills of the students and they take charge in controlling the credit card usage of their children. Data also showed that the two most common reasons for the use of credit cards were convenience and safety. Majority of the college students use their credit cards at least once a week and charge an average of Php 4,894.64 per month. Furthermore, the students use credit cards primarily for purchasing clothing, shoes, and meals. Overspending and impulse buying showed to be the major problems encountered in using credit cards. Recommendations for further research are provided at the end of the paper.